Reproductive rights on the path of liberation: from deconstructing the concept of control in our society to emphasizing pro-attachment attitudes. (6th February 2020) - Giroux, Caroline; Hategan, Ana; Bourne, Christina
Abstract: The debate about abortion is recurrently pervading not only politics and public health but also society at large, even within the utilization of mass media. The authors reinforce that access to reproductive health is a human rights issue and discuss facts and misconceptions associated with the procedure. They reframe the discussion and scripts sometimes found in pop culture, illuminating how attitudes towards reproductive rights may affect people. To address the polarization impasse, they propose using the lens of attachment relationships and offer corresponding solutions on three core levels: educational, social and narrative.